Econometric estimation of investment factors in agro-industrial production of Ukraine - Voloshyn, Volodymyr; Kucher, Roman-Danyil (Technology audit and production reserves, 2017)
Investments in agro-industrial production of Ukraine are the object of research. A characteristic disadvantage of the object of research is the dynamism of the indicators and dependence on natural and climatic conditions. Introduction of innovative forms of production of agro-industrial products would allow to partially reduce the influence of external factors on the production process and, as a result, make the agro-industrial complex more attractive for investment, in particular for foreign investors. In the course of the study, the authors use the method of econometric estimation of investment factors in the agro-industrial production of Ukraine. According to the received calculations, the basis for asserting a high investment dependence on the economic efficiency of the industry (regression coefficient is 0.29) and its environmental sustainability (0.27). At the same time, it is somewhat less, but also the staffing support of the enterprises of the industry (0,13) also makes a positive impact on the volume of investment. The low level of the efficiency of the functioning of the industry is established and proved (the integral coefficient in 2015 was 0.383 and decreased from 2011 to 0.004), which indicates its low investment attractiveness, which is deteriorating. It is identified that the main factor that led to this is the deterioration of the economic efficiency indicators of the industry (the integral index dropped to 0.332 in 2015) and environmental sustainability (up to 0.159).